Stochastic homeostasis in human airway epithelium is achieved by neutral competition of basal cell progenitors - Vitor H Teixeira; Parthiban Nadarajan; Trevor A Graham; Christodoulos P Pipinikas; James M Brown; Mary Falzon; Emma Nye; Richard Poulsom; David Lawrence; Nicholas A Wright; Stuart McDonald; Adam Giangreco; et al. (eLife, 2013)
Lineage tracing approaches have provided new insights into the cellular mechanisms that support tissue homeostasis in mice. However, the relevance of these discoveries to human epithelial homeostasis and its alterations in disease is unknown. By developing a novel quantitative approach for the analysis of somatic mitochondrial mutations that are accumulated over time, we demonstrate that the human upper airway epithelium is maintained by an equipotent basal progenitor cell population, in which the chance loss of cells due to lineage commitment is perfectly compensated by the duplication of neighbours, leading to “neutral drift” of the clone population. Further, we show that this process is accelerated in the airways of smokers, leading to intensified clonal consolidation and providing a background for tumorigenesis. This study provides a benchmark to show how somatic mutations provide quantitative information on homeostatic growth in human tissues, and a platform to explore factors leading to dysregulation and disease.